Assessment of genetic diversity based on agro-morphological traits and genic microsatellite markers in inter-specific derivatives and cultivars of pigeonpea - Durgesh, Kumar; Raje, R.S.; Singh, Anand K; Singh, A.M.; Pandey, Avinash; Singh, N.K. (The Indian Journal of Genetics and Plant Breeding, 2016)
In the present study, genetic diversity among 73 genotypes comprising of cultivars and stable inter-specific derivatives from pigeonpea (Cajanus cajan x C. scarabaeoides) was assessed based on thirteen agro-morphological and quality traits and 42 genic microsatellite markers. Cluster analysis based on Tocher’s methods of pooled fielddata of agromorphological traits from all three environment and two locations grouped pigeonpea genotypes into nine clusters. Genetic divergence was mainly contributed by days to 50% flowering (30.14%) followed by100 seed weight (20.78%) and protein content (12.56%). The range of polymorphic information content (PIC) for microsatellites was 0.055- 0.695. A total of 104 alleles were amplified with 42 SSR markers with an average of 2.48 alleles per locus.Ten alleles were unique to inter-specific derivatives. Based on Shannon’s information index (I), ASSR 17 was the most informative locus for all the genotypes. Two loci, ASSR114 and ASSR317 were polymorphic only among the interspecific derivatives. Cophenetic correlations were statistically significant for phenograms based on Euclidean distances and average Manhattan distance analysis. The first three principal coordinates explained 60.17% and 57.22% of the accumulated variation in case of agromorphological traits and microsatellite data respectively. The information accrued is potential for broadening the genetic base in pigeonpea.